Trabalho docente na educação física no Espírito Santo - Pozzatti, Mariana (2012)
This study deals with the conditions of teaching work in physical education at Espírito Santo basing in discussions on the "state of knowledge" of the subject area and in the data of the national survey: "Teaching Work in Basic Education in Brazil", held in 2009. The locus of research focused on municipalities Guarapari, Nova Venécia, Santa Teresa, Viana and Vitoria. In the production and discussion of the data, were approached seventy questions of the data collection instrument used in the national survey, which dialogued with the production of authors like Emile Tenti Fanfani, Maurice Tardif, Claude Lessard, Joarez Vieira do Nascimento, Jorge Both, Vicente Molina Neto and other researchs located in the "state of knowledge". Aimed to know and understand how the teacher of physical education been developing his work nationally and especially in the public schools of basic education in the municipalities investigated in the Espírito Santo, with the guiding principles the following questions: who is the teacher of Physical Education active in our state? How these professionals organize their work? What are their conditions of work and career? It was concluded in the study that, in general, the situation faced by teachers of physical education in the Holy Spirit is similar to other regions of Brazil, especially in relation to constituents aspects of teaching, training, infrastructure, workload and pay. However, the state presented differentiated data regarding the gender of professionals, being quite close the number of male teachers and female. It was evident, finally, the need to rethink the training of teachers and the ways to approach and appropriation of the documents that guide their work.